การพัฒนารูปแบบการจัดลำดับความสำคัญของปัญหาในกระบวนการดำเนินงานอนามัยชุมชน (SPS Model) สำหรับการฝึกภาคปฏิบัติของนักศึกษาพยาบาลในรายวิชาปฏิบัติการพยาบาลครอบครัวและชุมชน2 - Phalakan, Boonchai (วารสารวิจัยการพยาบาลและสุขภาพ, 2019)
การจัดลำดับความสำคัญของปัญหาในกระบวนการดำเนินงานอนามัยชุมชน มีความสำคัญและท้าทายในการแก้ปัญหาในชุมชน คณะผู้วิจัยจึงได้ทำการศึกษาและพัฒนารูปแบบการจัดลำดับความสำคัญของปัญหาในกระบวนการดำเนินงานอนามัยชุมชน (SPS Model) สำหรับการฝึกภาคปฏิบัติของนักศึกษาพยาบาลในรายวิชาปฏิบัติการพยาบาลครอบครัวและชุมชน 2 การวิจัยครั้งนี้มีวัตถุประสงค์ เพื่อพัฒนาและประเมินประสิทธิผลรูปแบบการจัดลำดับความสำคัญของปัญหา (SPS Model) ที่พัฒนาขึ้นโดยใช้รูปแบบการวิจัยและพัฒนา (Research and Development)โดยแบ่งการศึกษาออกเป็น 2 ระยะ ได้แก่ 1.ระยะสร้างและพัฒนารูปแบบ กลุ่มตัวอย่างเป็นนักศึกษาพยาบาลนักศึกษาพยาบาลศาสตร์ชั้นปีที่ 4 และอาจารย์ที่เกี่ยวข้อง จำนวนรวม 74 คน และ 2.ระยะประเมินประสิทธิผลของรูปแบบกลุ่มตัวอย่างประกอบด้วย นักศึกษาพยาบาลศาสตร์ชั้นปีที่4อาจารย์ผู้สอนภาคปฏิบัติ อาจารย์พี่เลี้ยงในแหล่งฝึก และประชาชนผู้มีส่วนร่วมในกระบวนการ รวมทั้งสิ้น 184 คนเครื่องมือที่ใช้คือรูปแบบการจัดลำดับความสำคัญของปัญหา (SPS Model) ที่พัฒนาขึ้นและแบบประเมินประสิทธิผลของ Model ประกอบด้วยการแบบประเมินใช้ได้และความพึงพอใจต่อการใช้ของModel แบบประเมินการรับรู้และทัศนคติต่อ การใช้Models และแบบสัมภาษณ์กึ่งโครงสร้าง วิเคราะห์ข้อมูลโดยใช้สถิติพรรณนา และวิเคราะห์เชิงเนื้อหาผลการวิจัย 1.รูปแบบการจัดลำดับความสำคัญของปัญหาในกระบวนการดำเนินงานอนามัยชุมชน (SPS Model) มีการพัฒนา ทดลองใช้ ปรับปรุงตรวจสอบ แก้ไขจนได้รูปแบบการจัดลำดับความสำคัญของปัญหาในกระบวนการดำเนินงานอนามัยชุมชน (SPS Model) ที่มีความเหมาะสมสำหรับการใช้ในการฝึกภาคปฏิบัติของนักศึกษาพยาบาล2.ผลการประเมินประสิทธิผลของ SPS Model พบว่าระดับคะแนนในทุกหัวข้ออยู่ในระดับมาก (mean = 3.64, SD ± 0.98) คะแนนเฉลี่ยความพึงพอใจ (mean = 4.08, SD ± 0.78) และคะแนนเฉลี่ยของทัศนคติต่อ Model โดยภาพรวม อยู่ในระดับมาก (mean= 5.68, SD ± 1.08) ข้อมูลเชิงคุณภาพพบว่าว่า SPS Model เป็นวิธีการที่ดี ง่ายต่อการนำไปใช้ และมีความเหมาะสมในการใช้ฝึกภาคปฏิบัติของนักศึกษา The Development of SPS Model Priority Setting Method for Nursing Student Designed for Family and Community Nursing Practicum2 Prioritizing problems in the community health process is important and challenge to solve problems in the community. Researchers and teams have developed a SPS Modelfor prioritizing problems in the community health process for practical training of nursing students in family and community nursing practicum 2.This research aimed to develop and evaluate the SPS Model for prioritizing problems in community health for nursing students in family and community nursing practicum 2. There were two phases of this study including; 1) the model development phase, the samples were 74 of the 4th years nursing students and nurse instructors, and 2) the evaluation of effectiveness model phase, the samples were 184 of the 4th nursing students, nurse instructors and preceptors.The research tools were the SPS Model and effective evaluation tools that including usability and satisfaction questionnaire, attitude using of the SPS Model and the semi-structured interviewed. Data were analyzed using descriptive statistics, and content analysis was used.The results found 1) the process and development model of prioritizing problems in community(SPS Model)was developed and implemented that improved to applicable for nursing students in family and community nursing practicum 2. And 2) the evaluation of the effectiveness of SPS Model found, that usability in high level (mean = 3.64, SD ± 0.98), satisfaction in high level (mean = 4.08, SD ± 0.78)respectively. Overall Perception and Attitude for SPS Model in high level (mean = 5.68, SD ± 1.08). Qualitative results shown that The SPS Model was feasibility, and was aligned with the purpose of prioritizing problems, and applicable for practice in nursing students.There were few that indicate The SPS Model was difficult to use. In the conclusions, the model for prioritizing problems in the community health process (SPS Models) is usable and applicable to use for the practice of students. However, it should be prepared nurse students before practice regard to the detailed use and explanation of each topic of The SPS Model. Thus, the nurse students understand to continue for implement effectively.